Lactobacillus paracasei microencapsulados com alginato de cálcio revestidos com gelatina: sobrevivência in vitro e aplicação em bebidas à base de oleaginosas - Conceição, Rosetania Correia Neves da (Universidade Federal do Tocantins, 2017)
The survival of two strains of Lactobacillus paracasei (LBC81 and ELBAL) coencapsulated with fructooligosaccharides (FOS) in calcium alginate coated with or without gelatin were evaluated at pH 1.5, in the presence of 1% and 2% of bile salts and storage at 4°C. The yield of the microencapsulation and the size of the microcapsules were evaluated. The size of the gelatin uncoated microcapsules varied among 1.5 and 1.7 mm and those coated presented variation among 1.8 and 2.0 mm. The yield of the microencapsulation was 59% to 73%. Microencapsulated probiotics were resistant to low pH, presence of bile salts and to low temperatures storage, presenting cell viability above 8,0 Log CFU/mL for 35 days, and free cells did not resist under the same conditions. Lactobacillus paracasei (LBC81) microencapsulated with 1.5% FOS coated with gelatin were able to ferment water soluble extracts of Brazil nuts and baru, separately. The fermented water soluble extracts presented desirable characteristics of pH (5,5) and lactic acid concentration (1,4%) within the standards required for this type of beverage during fermentation and after 21 days of storage. The cell population during and after the refrigerated storage was 9,5 Log UFC/mL, above that recommended by the United Nations Food and Agriculture Organization (FAO) to cause consumer health benefits. The extracts can be used commercially for the production of new functional beverages. This is the first study in which microencapsulated probiotics have been used for the development of oleaginous based beverages.